Determinants of Leprosy Incidence in West Bekasi, Indonesia: A Cross-Sectional Study - Nadya Agustin; Haerudin Haerudin; Retno Anggraeni Puspita Sari; Cicilia Nony Ayuningsih Bratajaya (STIKep PPNI Jawa Barat, 2025)
Background : Leprosy remains a chronic infectious disease that can lead to long-term disability when diagnosis and treatment are delayed. Caused by Mycobacterium leprae, the disease primarily affects the skin and peripheral nerves and continues to pose public health challenges in several endemic regions, including parts of Indonesia. Understanding the factors associated with leprosy incidence is essential for developing effective prevention and control strategies. Objective : This study aimed to identify factors associated with the incidence of leprosy at the Danau Indah Cikarang Barat Community Health Center, Bekasi Regency. Methods : A quantitative study with a cross-sectional design was conducted involving 90 respondents selected through purposive sampling. The independent variables examined included age, sex, socioeconomic status, educational level, knowledge, history of contact with leprosy patients, personal hygiene practices, environmental conditions, and access to health information media. Data were collected using structured questionnaires and analyzed using the Chi-square test with a significance level set at 0.05. Results : The analysis revealed statistically significant associations between leprosy incidence and contact history, socioeconomic status, personal hygiene, and environmental conditions (p < 0.05). In contrast, age, sex, educational level, and access to information media were not significantly associated with leprosy incidence. Conclusion : The findings indicate that leprosy incidence is strongly influenced by social, behavioral, and environmental factors. Strengthening health education, improving environmental sanitation, and enhancing early detection and treatment programs are essential to reduce leprosy transmission in endemic areas. These results may serve as valuable input for healthcare providers and policymakers in developing targeted leprosy prevention and control initiatives.